SISTEM INFORMASI PENGELOLAAN EKONOMI KREATIF BERBASIS WEB MENGGUNAKAN METODE SCRUM (STUDI KASUS DINAS PARIWISATA KAB CIAMIS) - Herdiana; Dwicahya Supriatman, Rian; Maulana, Haisyam (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
Ciamis Regency has substantial potential in the creative economy (Ekraf) sector, yet management remains constrained by manual and decentralized data collection. This study designs and implements a web-based Ekraf Management Information System to support integrated data collection, online registration, data verification, report generation, and public business profiles for promotion. Development follows the Scrum methodology to enable iterative and adaptive delivery, using PHP–Laravel, MySQL, and XAMPP. System modeling employs UML (use case, activity, class, and sequence diagrams). Functional evaluation applies black-box testing across core modules (registration, Login, submission, verification, and reporting). Results show that all test scenarios meet acceptance criteria business processes become more efficient and transparent, and service access for business actors improves. The system also consolidates Ekraf data digitally and disseminates business information online. At present, the solution is functionally feasible and under submission for adoption by the Ciamis Tourism Office. Future work includes integration with licensing services (NIB/OSS), dashboard analytics, automated notifications, and performance optimization for larger data scales.